2019
DOI: 10.4236/ojst.2019.91002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication for Oral Health Problems among Dental Outpatients at a Nigerian Tertiary Hospital

Abstract: Background: Self-medication is the inappropriate use of drugs to treat self-diagnosed disorders or symptoms. Even though Self-medication has benefits as it enhances better use of clinical skills and increases access to medication; it is also associated with risks such as adverse drug reactions and antibiotics resistance. Objectives: To determine prevalence of self-medication practices among dental outpatients , triggering factors that influence self-medication practice and common source of drugs. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…According to the findings of this study, Ibuprofen and salt/water mouthwash was the most common agent used for self-medication, which was predictable because toothache was the most frequent problem. Previous studies reported that analgesics were the most frequent agents used for self-medication (1,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of this study, Ibuprofen and salt/water mouthwash was the most common agent used for self-medication, which was predictable because toothache was the most frequent problem. Previous studies reported that analgesics were the most frequent agents used for self-medication (1,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio se demostró que el 45,6% de los pacientes se automedicaban para aliviar el dolor dental, de igual manera que en los estudios realizados por Navabi 24 en Kerman (Irán), con el 44,3%; Nayyar 25 en Karnataka (India), con el 83,6%; y Olawuyi 26 en Lagos (Nigeria), con el 71%. Esto podría deberse a que el dolor principal se da en la zona bucal y, para la percepción de los pacientes, no es una enfermedad grave.…”
Section: Discussionunclassified
“…In Nigeria, patients visit patent medical stores or pharmacies for immediate care before thinking of going to a dentist. [ 20 ] In the last decade, a lot of effort was put into changing the role of the CPs from traditional drug dispensing to a provider of public health services. [ 21 ] However, there is a dearth of published information on pharmacists’ knowledge of oral health care in South East Nigeria.…”
Section: Introductionmentioning
confidence: 99%